CRM PRACTICES IN ORIENTAL BANK OF COMMERCE AND HDFC BANK – A COMPARATIVE STUDY - Pawar, I. Anand; Dasari, Usha (International Journal For Research In Business, Management And Accounting, 2020)
The idea of Customer Relationship Management (CRM) is that it helps businesses use technology and human resources gain insight into the behaviour of customers and the value of those customers. If it works as hoped, a business can: provide better customer service, make call centers more efficient, cross sell products more effectively, help sales staff close deals faster, simplify marketing and sales processes, discover new customers, and increase customer revenues. It doesn't happen by simply buying software and installing it. For CRM to be truly effective an organization must first decide what kind of customer information it is looking for and it must decide what it intends to do with that information. The Indian banking sector is trying to survive this dynamic challenge of winning more and more customers and retaining them by giving customised services. Now, more and more banks are increasingly getting customer-focused by implementation of CRM. This paper presents a research study on status of the adoption and use of CRM in banking sector as a comparative study in Hyderabad city. For this a sample of 100 (50 each from select private and public sector banks) were considered in this study to understand the multi-dimensional setup of customer relationships and its effects in competitive banking environment.